2016
DOI: 10.3390/w8030092
|View full text |Cite
|
Sign up to set email alerts
|

Differing Levels of Forestry Best Management Practices at Stream Crossing Structures Affect Sediment Delivery and Installation Costs

Abstract: Forestry best management practices (BMPs) are used to reduce sedimentation from forest stream crossings. Three BMP treatments (BMP´, BMP-std, and BMP+) were applied to three forest road stream crossings (bridge, culvert, and ford). BMP´did not meet existing BMP guidelines, BMP-std met standard recommendations, and BMP+ treatments exceeded recommendations. Following BMP applications, three simulated rainfall intensities (low, medium, and high) were applied in order to evaluate sediment delivery from crossing ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Culverts are advantageous for logging roads because they are simple to install, can carry heavy payloads without complex calculations of weight limits, and can be either temporary or permanent (Morris et al. ). Disadvantages of culverts include placement of fill dirt in the stream channel with associated sedimentation, improper sizing for water yields, increased downstream water velocity and scouring, restriction of stream aquatic passage, and problems associated with culverts becoming clogged (Warrington et al.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Culverts are advantageous for logging roads because they are simple to install, can carry heavy payloads without complex calculations of weight limits, and can be either temporary or permanent (Morris et al. ). Disadvantages of culverts include placement of fill dirt in the stream channel with associated sedimentation, improper sizing for water yields, increased downstream water velocity and scouring, restriction of stream aquatic passage, and problems associated with culverts becoming clogged (Warrington et al.…”
Section: Resultsmentioning
confidence: 99%
“…However, fords tend to allow increased stream sedimentation due to the repeated churning of stream sediments, and their use is limited by appropriate weather conditions (Morris et al. ). We found that fords were used for 12%–28% of the haul road crossings across all regions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations